Personalized virtual reality simulation training system for percutaneous needle insertion and comparison of zSpace and vive. (July 2022) - Zhou, Zeyang; Yang, Zhiyong; Jiang, Shan; Jiang, Bowen; Xu, Bin; Zhu, Tao; Ma, Shixing
Abstract: Purpose: In this research, we present a personalized simulation training system for percutaneous needle insertion based on virtual reality (VR). Within this system, surgeons can become more familiar with real surgical procedures, thereby reducing errors that may occur in real surgery. Additionally, different VR technologies, i.e., zSpace and Vive, were compared to provide surgeons with a better surgical training environment. Methods: and Methods A VR system combined with the treatment planning system was developed to create personalized patient training environment. An evaluation study recruiting twenty novices was performed to demonstrate the system. Each participant performed six independent needle placements using the VR system. Placement time was recorded. Placement error was defined as the distance from the needle tip to the target center. The participants completed a seven-point Likert scale questionnaire after the simulation. Results: Compared with Vive, using zspace reduces the placement time (from 90.32 s to 68.94 s). The placement error using zSpace and Vive was similar (1.27 ± 0.68 mm, 1.56 ± 0.81 mm, respectively). The questionnaire survey results show that most participants are highly satisfied with the training effect of the VR system. Participants prefer the operation mode and convenience of zSpace but think that the immersion of Vive is better. Conclusions: The personalized virtual reality surgical training system was effective as a training system for percutaneous needle insertion. The system based on zSpace had a shorter placement time while maintaining placement accuracy compared to the system based on Vive. The system based on zSpace achieved higher satisfaction in most aspects except for immersion.